PENDIDIKAN BERBASIS KOMPETENSI DALAM PERSPEKTIF AJARAN ISLAM - Abdul Rozak (el-Moona: Jurnal Ilmu Pendidikan Islam, 2021)
Competency-based education is education that emphasizes the abilities that must be possessed by graduates in a level of education. Article 1 paragraph 1 of the 2003 National Education System Law states that: "Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character and skills needed by himself, society, nation and state. Competency-based education was rolled out in 2004 after the implementation of the Competency-Based Curriculum (KBK). Moving on from this main idea, this was the basis for searching and researching from the point of view of Islamic teachings regarding competency-based education which was studied from written materials from available books.